Perspectivas de la educación ambiental instaladas en profesores: reflexión de las creencias y obstáculos - Espitia Ruiz, Gloria Yolima (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Recently, the need to innovate has been reiterated and for this, several sectors of society are concerned about achieving a balance in the ecosystem, including the education area. This article presents a qualitative methodological approach in which a reflection of the literature is made, about the beliefs and perspectives that teachers have about environmental education and its teaching, as well as the main obstacles that interfere in the teaching of environmental education contents. When making a reflection of the literature, the article considers that teachers commonly identify environmental education with ecology, the environment or confuse it with PRAES; In addition, they do not apply the transversal structure to the  curriculum, but  they take it as a subject in the area of natural sciences. As a result, the need for teachers to reflect and, if possible, transform the conceptions and application of environmental education in the school is highlighted